Enjeux et perspectives en éducation thérapeutique du patient : des soignants formés en sciences de l’éducation - Carole Baeza (Recherches en Éducation)
The increasing number of programs in Therapeutic Patient Education (TPE) available in colleges and in-house training illustrate the growing emphasis placed on the education of health care professionals in society.The latest French Public Health Law dated July 21st, 2009 clearly recognizes TPE as a core discipline and therefore actively promotes patient-centered care in parallel to the existing curative treatment protocols.Health care professionals looking to add patient-centered care to their curative practice increasingly enrol in education-oriented courses, including, as far as we are concerned here, in Education Science courses. We do witness a paradigm shift in our approach to patient care, leading to a multidisciplinary effort to bridge the gap between psychosocial and purely therapeutic treatment (in a joint effort to promote patients’ self-management, prevention strategies and strictly medical care).Health care providers are invited, through TPE, to re assess their patient management practice and share with their patients new strategies to educate them in order to establish a comprehensive treatment strategy, both for patients and health providers. In order to better understand the challenges of PTE and the goals of health care providers involved in Education Science, we conducted a qualitative study on the first two classes of TPE (students of 2008 to 2010) at the University of Rouen, Normandy (France). We will attempt to evaluate PTE students’ personal and professional evolution in relation to this new comprehensive approach to patient care.